Psychology in Brazilian Assistance to the Insane: First Half of the 20th Century - Facchinetti, Cristiana; Jacó-Vilela, Ana Maria (Universitas Psychologica, 2019)
This paper provides an overview on the history of the earliest applications of psychological practices in the two main mental institutions linked to the Assistance for Psychopaths in Rio de Janeiro, Brazil, in the beginning of the 20th Century. This encompassed a range of clinical practices that employed psychological techniques and tools thought as having a curative effect on the causes or symptoms of mental illness. Mental hygiene doctors used those techniques as well, with the biopolitical goal of averting illness and any consequent risk and social danger. The techniques are analyzed in their relation to the modernization project of Brazilian nation and to the problem of what was then understood as its “degenerated population”. The main objective of the paper is to investigate the role of Psychology in Brazil in the early 20th Century. The results appoint an effective interrelation between the raise of scientific legitimacy of Psychological knowledge and technology and the integration of Psychiatry within different nation's modernization projects.
Number: 5
Keywords: higiene mental

Sociedade Brasileira de Psicanálise do Rio de Janeiro (SBPRJ) – 1959- - Facchinetti, Cristiana (Dicionário histórico de instituições de psicologia no Brasil, 2011)

Sociedade Psicanalítica do Rio de Janeiro (SPRJ) – 1955 - Facchinetti, Cristiana (Dicionário histórico de instituições de psicologia no Brasil, 2011)

Hospital Nacional de Psicopatas – 1927-1943 - Facchinetti, Cristiana (Dicionário histórico de instituições de psicologia no Brasil, 2011)

Psicologia, cultura e história: perspectivas em diálogo - Jacó-Vilela, Ana Maria; Mahfoud, Miguel; Massimi, Marina; Facchinetti, Cristiana; Dantas, C.; Sanchis, P. (Outras Letras, 2012)
Originários do XIII Simpósio de Intercâmbio Científico em Psicologia da Anpepp , os cinco artigos contribuem para a discussão acerca dos processos de subjetivação e de suas relações com as culturas. Uma coletânea que auxiliará ao ensino de graduação em História da Psicologia, Psicologia, Psicologia Social e Psicologia da Cultura e aos apreciadores dos vários percursos e interpretações do pensamento psicológico
Keywords: Psicologia